Perancangan Identitas Visual Yessika Roti - Nugraha, Fimalian; Tarmawan, Irwan (Fakultas Desain Universitas Komputer Indonesia, 2022)
Because humans continue to grow then change, technology continues to develop, and brand competition is increasingly fierce, to be able to compete with other brands in the current era, Yessika Roti tries to keep up with the times to adjust to consumers in the current era, while caring for consumers who might be affected by times, such as improving products and services. Even though parents already have customers, in seeing the potential of new customers in the current era, it is needed to expand market share to reach a younger age, to accelerate consumer turnover in various generations, both in identity, products, and services. So we need a visual identity that supports it all, while communicating updates and developments in the image of existing products or services, to strengthen the brand identity that is able to compete with other similar brands in the current era. But the visual identity that is used today is quite long, and the audience will have difficulty in knowing the improvements that will be made if there is no change, so that it requires designing a new visual identity, as an initial step to support an increase in market share that will be done.